Le Rôle de mandataire donné aux architectes dans la consultation de 2008 sur le Grand Paris : quels effets sur les collaborations interprofessionnelles ? - Guillaume Duranel (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Following a doctorate thesis in 2019, this article explores the modes of cooperation that took place during the 2008 Grand Paris competition and in the Atelier international du Grand Paris (AIGP). The role granted to architects who were representatives of the groups gives rise to a specific investigation into the way in which this dominant position imposes forms of work onto a wider group of professionals. By examining the relationships that develop between the architect and their various partners, this article identifies conventional patterns integrated into the agencies’ organizations and which are transposed on the occasion of other types of collaboration.